DRUG-RESISTANT EPILEPSY – CURRENT TREATMENT STRATEGIES AND FUTURE THERAPEUTIC PERSPECTIVES - Honorata Juniewicz; Zuzanna Kudlińska; Ryszard Łagowski; Julia Kosęda; Anna Jędrasiak; Jakub Piotrowski; Patryk Heryć; Karolina Kananowicz; Zofia Laska; Marianna Latour (International Journal of Innovative Technologies in Social Science, 2025)
Drug-resistant epilepsy is a chronic neurological disorder characterized by persistent seizures despite the use of appropriate pharmacotherapy. This condition significantly deteriorates patients’ quality of life, in-creases the risk of psychiatric disorders, and contributes to more frequent hospitalizations. Despite consid-erable progress in the development of new generations of antiepileptic drugs, there remains a pressing need to explore innovative therapeutic strategies. This article presents treatment approaches including pharmacotherapy, neurostimulation techniques, and the use of surgical interventions in epilepsy manage-ment. Special attention is given to targeted therapies that take into account genetic, immunological, and metabolic mechanisms of epilepsy. Although these therapies hold the potential for treatment, their imple-mentation is associated with numerous challenges, high costs, and the necessity for procedural standardi-zation. The article emphasizes the need for interdisciplinary collaboration and further research to improve treatment efficacy for patients suffering from drug-resistant epilepsy.